Eccentric exercise in alpine skiing - Hoppeler, H.; Vogt, M. (Science and Skiing IV, 2008)
INTRODUCTION: The muscle recruitment pattern during alpine skiing is special and characterized by a preponderance of eccentric (lengthening) over concentric (shortening) activity (Berg & Eiken 1999). Eccentric contractions have specific physiological characteristics which have not been studied nearly as well as those of concentric muscle contractions. The key features of eccentric contractions are a much lower (approx. fourfold) metabolic requirement for a given (negative) power requirement combined with a close to twofold reduced recruitment of motor units, ie. smaller EMG activity, for a given (negative) torque. It is surprising that in general, training regimes in alpine skiing have not been tailored to more specifically address the problem of improving and controlling eccentric contractions.